Total Synthesis of a Mycolic Acid from Mycobacterium tuberculosis - Tahiri, Nabil (John Wiley and Sons Inc., 2020)

(untitled) (Angew Chem Int Ed Engl)
In Mycobacterium tuberculosis, mycolic acids and their glycerol, glucose, and trehalose esters (“cord factor”) form the main part of the mycomembrane. Despite their first isolation almost a century ago, full stereochemical evaluation is lacking, as is a scalable synthesis required for accurate immunological, including vaccination, studies. Herein, we report an efficient, convergent, gram‐scale synthesis of four stereo‐isomers of a mycolic acid and its glucose ester. Binding to the antigen presenting protein CD1b and T cell activation studies are used to confirm the antigenicity of the synthetic material. The absolute stereochemistry of the syn‐methoxy methyl moiety in natural material is evaluated by comparing its optical rotation with that of synthetic material.